Imobilização de Triclosan e Eritrosina em filmes ultrafinos para estudos de inativação de microrganismos - Pedro, Maria Fernanda da Costa (2017)
The use of the layer-by-layer (LbL) deposition technique allows materials such as drugs to be self-assembly in multilayers with other electrolytes by combining their properties in a nanostructured system. Triclosan is commonly used as a drug because of its bactericidal action, while erythrosine has been used as a photosensitizer in photodynamic therapies because of its high light absorptivity in the visible region of the electromagnetic spectrum. The major advantage of investigating immobilized in LBL film systems is the benefit of characterizing the interaction through available for the substance in solid state techniques. It was possible to immobilize in LbL films, ERY and ERY+TCS films. The results show that the growth of the films is linear indicating the deposition of the same amount of material from the first bilayer without substrate interference. The release analysis showed slow kinetics, which occurred more rapidly for PAH/ERY LbL films, probably due to the results of apparent activation energy, which were higher for films with TCS. The combination of the TCS, ERY and laser light (532 nm) for photodynamic inactivation of the fungus Candida albicans were analyzed and the results are promising for future studies in applications such as coatings surfaces of dental implants, for example.